PENGARUH MULTIMEDIA INTERAKTIF TERHADAP HASIL BELAJAR SISWA KELAS XII PROGRAM KEAHLIAN AKUNTANSI PADA MATERI ENTRI JURNAL KHUSUS DI SMK LABOR BINAAN FKIP UNRI PEKANBARU - Sri Wahyuni; Gimin Gimin; Hendripides Hendripides (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2018)
Abstract: This study aims to determine the effect of the use of interactive multimedia on the learning outcomes of students of class XII Accounting Skills Program on the material of special journal entries in the Labor Vocational High School of the FKIP guided by UNRI Pekanbaru. This research was conducted on 17-20 July 2018. The research method used was quasi experimental design with the type of Nonequivalent Control Group Design. Sampling uses class sample techniques. The research sample amounted to 67 students, consisting of 35 control class students and 32 experimental class students. The research instruments used were tests, observation sheets and questionnaire. The test instrument consisted of objective questions and transaction document questions, the observation sheet consisted of a multimedia physical observation sheet, teacher activity observation sheet and student activity observation sheet, and interactive multimedia benefit questionnaire instrument. Data analysis using gain values obtained results of 0.53 which fall into the medium category. Then analysis of the data of the two groups using the independent two sample t-test was obtained 0.046 at the significance level p < 0.05. It can be concluded that the use of interactive multimedia has an effect on student learning outcomes, and differences in learning outcomes in both groups show that the learning outcomes of students taught using interactive multimedia are better than students taught by using power point slides.Key Words: Interactive Multimedia, Learning Outcomes